Expression of Gαq Is Decreased in Lymphocytes from Primary Sjögren’s Syndrome Patients and Related to Increased IL-17A Expression - Yuechi Sun; Ying Wang; Shiju Chen; Guihua Fan; Junhui Zhang; Fan Dai; Hongyan Qian; Yuan Liu; Guixiu Shi (Journal of Immunology Research)
Primary Sjögren’s syndrome (pSS) is a rheumatic disease characterized by the destruction of salivary and lacrimal glands, and its pathogenesis mechanism remains unclear. Gαq is the α-subunit of the heterotrimeric Gq protein. Researches demonstrated that Gαq was involved in the pathogenesis regulation of several rheumatic diseases. This study explored the role of Gαq in pSS. Gαq mRNA levels in peripheral blood mononuclear cells (PBMCs) from 39 patients and 26 healthy controls (HCs) were investigated using real-time PCR. IL-17A serum concentrations in 22 pSS patients and 23 HCs were tested by ELISA, and the clinical significance of Gαq was analyzed. The association of Gαq with interleukin-17A (IL-17A) expression was also analyzed in patients with pSS. We showed that Gαq expression in PBMCs from patients with pSS was significantly lower than that in PBMCs from HCs. Gαq expression level was closely associated with pSS disease activity. Furthermore, a negative association was also found in IL-17A and Gαq expression level. These data suggest that Gαq is involved in pSS pathogenesis regulation, possibly due to its regulation of Th17. These results provide new insights into the pSS pathogenesis mechanism involving abnormal Th17 regulation.